Tinjauan Filsafat Pendidikan terhadap Pemikiran Pendidikan Islam Syekh Sulaiman Ar-Rasuli - Silva, Ray; Fatimah, Siti (Jurnal Kronologi, 2024)
This research aims to review the educational thoughts of Syekh Sulaiman Ar-Rasuli from the perspective of educational philosophy, focusing on moral education, humanism, and value education within the context of Islamic education in Indonesia. Through the reform of traditional education systems into madrasah, Syekh Sulaiman Ar-Rasuli was able to preserve classical values while adapting education to meet the needs of society. This study employs library research methodology with thematic analysis, where literature related to philosophical thought and concepts of Islamic education is analyzed in depth. The results of the study indicate that the thoughts of Syekh Sulaiman Ar-Rasuli align moral education, humanitarian values, and ethics with an ultimate goal that brings goodness to individuals and society at large. The relevance of these thoughts is not only evident in his time but also holds great potential for the development of modern Islamic education that emphasizes moral values and humanism as a foundation for shaping virtuous character.